Mindset Wirusaha : Strategi Menavigasi Dunia Bisnis yang Penuh Perubahan - Harun Puling; Marten Bainkabel; Wiranto Wiranto; Yosia Belo (Pusat Riset dan Inovasi Nasional, 2025)
In a rapidly evolving and uncertain business environment, having the right entrepreneurial mindset is crucial for long-term success. This article examines various strategies that entrepreneurs can apply to navigate the ever-changing business landscape. The main focus is on the importance of adapting to change, continuous innovation, effective risk management, and developing mental and emotional resilience. Additionally, the article highlights the significance of flexibility, inspirational leadership, and the ability to collaborate in facing dynamic market challenges. By cultivating a creative mindset, being open to feedback, and thinking long-term, entrepreneurs can leverage opportunities arising from change and ensure the sustainability of their businesses. The article concludes that an adaptive and innovative entrepreneurial mindset is the key to overcoming the increasingly complex business challenges and achieving success in a competitive market.